Exploring the Knowledge Gap and Implementation Challenges of Management Accounting Practices among the Farmer Business Groups within the Tanzanian Cocoa Sub-sector - Godfrey Frank Molela (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2026)
Studies have shown that knowledge and implementation of accounting practices, particularly management accounting (MA), pose significant challenges for small businesses in general, with limited attention given to small agribusiness groups. This study specifically explored knowledge gaps and challenges related to the implementation of MA practices among cocoa farmer business groups (FBGs) in Tanzania. Primary data were collected from 87 cocoa FBGs operating in the Kyela, Rungwe, and Kilombero districts, using a mixed research design. Qualitative data were analyzed through thematic analysis, while quantitative data were examined using one-way analysis of variance (ANOVA), supplemented by Tukey’s range and Dunnett’s tests. The findings revealed that Tanzanian cocoa FBGs possessed limited knowledge of MA practices. This condition, combined with a lack of awareness, unstructured business operations, financial constraints, and insufficient readiness among leaders, hindered effective implementation. These results highlight the critical need for FBG management to strengthen their knowledge of MA practices. Improving cocoa agribusiness structures and securing financing for operations, including the adoption of advanced accounting systems, are essential steps forward. Moreover, FBG leaders must be persuaded of the importance of MA practices in daily operations to foster willingness to adopt such systems.